The Role and Mechanism of Dendritic Cells in Cardiac Injury Repair - Liu, Jilong; Jing, Dong (Journal of Contemporary Medical Practice, 2025)
Acute inflammation around the myocardial infarct area promote the progression of heart failure post- myocardial infarction. Subsequently, adaptive immunity and anti-cardiac autoimmunity are also involved in. Monocytes recruited from bone marrow and spleen play an important role in myocardial injury and repair of myocardial infarction. Although, monocyte-derived macrophages have been extensively studied in myocardial injury, repair, and myocardial remodeling. Recently, more and more studies focus on the role of dendritic cells (DCs) in cardiac injury and repair after acute myocardial infarction, but the mechanismneeds further exploration. This review focus on discussing the role and prospects of dendritic cells in cardiac injury repair.